The influence of globalization processes on the socio-political outlook of the individual - Ulmashuzhaev Zoirhuzha Abbosovich (Genius Journals, 2022)
The article, on the basis of various sources, some aspects of the influence of globalization processes on the socio-political outlook of an individual are revealed. Also in it. Also, in the current period, the process of globalization is expanding, which affects the new look and development of the world political space. It was revealed that the global development of states in the world political space is, first of all, a new joint development of all countries and peoples of the world in political, economic, social, cultural, environmental and psychological terms
Keywords: Globalization; Information; Freedom Of Information; Internet